Characteristics of schools with and without Gay-Straight Alliances. Issue 4 (1st October 2020) - Baams, Laura; Pollitt, Amanda M.; Laub, Carolyn; Russell, Stephen T.
Abstract: Research shows that Gay-Straight Alliances (GSAs) are associated with school climate and student well-being, but it is unclear what school characteristics may account for some of these findings. The current study describes characteristics of schools with and without GSAs. Using a population-based sample of 1, 360 California public high schools, inferential statistics show that schools with larger enrollment, more experienced teachers, and lower pupil/teacher ratios were more likely to have GSAs. In addition, among schools with GSAs, larger enrollment, more experienced teachers, fewer socioeconomically disadvantaged students, and higher academic achievement are among the factors related to a longer presence of GSAs. Implications for GSA and policy implementation, as well as the importance of accounting for school characteristics in research on GSAs are discussed.